EFEKTIVITAS LAGU MODEL DALAM PENDIDIKAN KARAKTER ANAK USIA DINI DI RA AL-HAMIDY BALIKPAPAN - Jamilah, Jamilah; Astutik, Andri (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
This study aims to explore the effectiveness of model songs as a media for character education in early childhood at RA Al-Hamidy, Balikpapan. The main issues raised are the importance of character education at an early age and the potential of model songs in instilling character values. This research uses qualitative approach with case study design to deeply understand the implementation of model songs in learning activities. Data were collected through observation, interviews and document analysis. The results showed that model songs have a significant role in early childhood character building, with the ability to convey moral messages in a fun and easy-to-understand manner. Model songs are effective in instilling values such as honesty, cooperation and responsibility, and developing children's social-emotional skills. This effectiveness is influenced by factors such as song quality, teacher competence and environmental support. This study recommends optimizing the use of model songs, improving teachers' competencies and actively involving parents in supporting character education.